Structural model of self-defeating behaviors based on the basic psychological needs, moral identity and emotional self-awareness of young girls - Shadjoo, Rezvan; Ghanbaripanah, Afsaneh; Dortaj, Fariborz; Ghasemi, Masoud (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the fit of structural model of self-defeating behaviors based on basic psychological needs, moral identity and emotional self-awareness in young girls. Method: The present study was correlational and path analysis. The statistical population of the present study included all male and female graduate students of Tehran universities who were studying in the academic year of 2019-20, were selected by cluster sampling; And the Questionnaire of the Importance of Moral Identity for Self (Aquino and Reed, 2002), the Basic Psychological Needs Questionnaire (Guardia et al., 2000), the Academic Dishonesty Scale (Kabi et al., 1997), the Emotional Self-Awareness Questionnaire (Grant et al., 2002), The Cognitive and Self-Behavioral Scale (Cunningham, 2007) responded. Data were analyzed using structural equation modeling method by Amos software. Results: Findings showed that the structural model of self-defeating behaviors based on the basic psychological needs, moral identity and emotional self-awareness in young people has a good fit (RMSEA= 0.07, GFI= 0.90). There was a significant negative relationship between moral identity and self-defeating behaviors (P